2000
DOI: 10.1093/carcin/21.5.491
|View full text |Cite
|
Sign up to set email alerts
|

Activation of JNK, p38 and ERK mitogen-activated protein kinases by chromium(VI) is mediated through oxidative stress but does not affect cytotoxicity

Abstract: In this study we have explored the involvement of oxidative stress in Cr(VI)-induced JNK, p38 and ERK signaling pathways and their effects on Cr(VI) cytotoxicity in human non-small cell lung carcinoma CL3 cells. Exposure to K(2)Cr(2)O(7) markedly activated JNK and p38 and moderately activated ERK in a dose- (10-80 microM) and time-dependent (1-12 h) manner. The activated p38 decreased markedly and rapidly and the activated JNK decreased gradually when Cr(VI) was removed from the medium. Post-incubation of Cr(V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 69 publications
5
45
0
Order By: Relevance
“…MKP5 has been shown to be able to deactivate all MAPK members, with some selectivity for the JNK/SAPK members [63,64]. Cr-induced activation of ERK, JNK and p38 pathways has been shown in a number of different cell lines, while the activation pattern is dependent on the dose/duration of the exposure [57,[65][66][67]. It has been suggested that Cr(VI) can potentially activate inhibitory MKPs [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MKP5 has been shown to be able to deactivate all MAPK members, with some selectivity for the JNK/SAPK members [63,64]. Cr-induced activation of ERK, JNK and p38 pathways has been shown in a number of different cell lines, while the activation pattern is dependent on the dose/duration of the exposure [57,[65][66][67]. It has been suggested that Cr(VI) can potentially activate inhibitory MKPs [66].…”
Section: Discussionmentioning
confidence: 99%
“…Cr-induced activation of ERK, JNK and p38 pathways has been shown in a number of different cell lines, while the activation pattern is dependent on the dose/duration of the exposure [57,[65][66][67]. It has been suggested that Cr(VI) can potentially activate inhibitory MKPs [66]. The present data supports a role for Cr(VI) in MKP5 transcriptional upregulation, which may play a role in death resistance, as its upregulation was abrogated in the B-5Cr cells.…”
Section: Discussionmentioning
confidence: 99%
“…The data suggest that oxidative stress initiates ERK activation by H 2 O 2 . Second, mannitol (100 mM), a free radical scavenger with specificity for hydroxyl radical (Guyton et al, 1996;Chuang et al, 2000), also abolished the ability of H 2 O 2 to activate ERKs. Third, the iron chelator o-phenanthroline (100 M) (Guyton et al, 1996;Regan et al, 2001) (Stadtman and Berlett, 1998).…”
Section: Growth Factor Receptor and Metal-catalyzed Free Radical Formmentioning
confidence: 99%
“…Recently, p38 kinase has been implicated in the cytotoxicity of chemical carcinogens Chuang et al, 2000), scattering (Spector et al, 2000) and metastasis (Taguchi et al, 2000;Huang et al, 2000). The p38 kinase becomes activated by MKK3/6 and probably other kinases via PI3K (Raingeaud et al, 1996;Macfarlane et al, 1997).…”
Section: Introductionmentioning
confidence: 99%